Systematic review and meta-analysis of neurofeedback and its effect on posttraumatic stress disorder - Voigt, Jeffrey D.; Mosier, Michael; Tendler, Aron (Frontiers in Psychiatry, 2024)
Background: To date only one systematic review and meta-analysis of randomized controlled trials (RCTs) has evaluated the effect of neurofeedback in PTSD, which included only 4 studies and found an uncertainty of the effect of EEG-NF on PTSD symptoms. This meta-analysis is an update considering numerous studies have since been published. Additionally, more recent studies have included fMRI-NF as well as fMRI guided or inspired EEG NF. Methods: Systematic literature searches for RCTs were conducted in 3 online databases. Additional hand searches of each study identified and of systematic reviews and meta-analyses published was also undertaken. Outcomes evaluated the effect of neurofeedback vs. a control (active, sham, and waiting list) on their effects in reducing PTSD symptoms using various health instruments.Meta-analytical methods used were inverse variance random effects models measuring both mean and standardized mean differences. Quality and certainty of the evidence was assessed using GRADE. Adverse events were also evaluated. Results: Seventeen (17) studies were identified evaluating a total of 628 patients. Ten (10) studies were used in the meta-analysis.Results from all studies identified favored neurofeedback's effect on reducing PTSD symptoms including: BDI pretest-posttest (mean difference (MD): 8.30 (95% CI: 3.09 to 13.52; P=0.002; I 2 = 0%)); BDI pretest-follow-up (MD: 8.75 (95% CI: 3.53 to 13.97; P<0.00001; I 2 = 0%); CAPS-5 pretest-posttest (MD: 7.01 (95% CI: 1.36 to 12.66; P=0.02; I 2 = 86%)); CAPS-5 pretest-followup (MD: 10 (95% CI: 1,29 to 21.29; P=0.006; I 2 = 77%); PCL-5 pretest-posttest (MD: 7.14 (95% CI: 3.08 to 11.2; P=0.0006; I 2 =0%); PCL-5 pretest-follow-up (MD: 14.95 (95% CI: 7.95 to 21.96; P<0.0001; I 2 =0%). Other studies reported improvements using various other instruments. GRADE assessments of CAPS, PCL, BDI demonstrated a moderate/high level in the quality of the evidence that NF has a positive clinical effect. Conclusions: Based on newer published studies and the outcomes measured, NF has demonstrated a clinically meaningful effect size; with an increased effect size at follow-up. This clinically meaningful effect appears to be driven by newer fMRI guided NF and deeper brain derivates of it.